Development Of Sustainability Key Performance Indicators (KPIs): A Systematic Literature Review - Aulia Maray Obvius CESSARIA; Agus BANDIYONO (PT Keberlanjutan Strategis Indonesia, 2024)
This research aims to review the development of sustainability performance measurement indicators used around the world. The application of these indicators varies greatly because there is no standard that regulates sustainability performance measurement indicators. The Global Reporting Initiative (GRI) is one of the guidelines for the implementation of Sustainability Key Performance Indicators (KPIs). However, it does not rule out the possibility of companies adopting other systematics that are widely developed, such as the Sustainability Balanced Scorecard (SBSC). By conducting a Systematic Literature Review (SLR) approach, there are 8 articles as data in the study. Reference articles come from Scopus and Google Scholar database sources with restrictions on publication years 2019-2024. The selected articles discuss factors that become challenges and obstacles, measurement methods, and strategies for formulating sustainability performance indicators. The research results present a literature review of variations in sustainability performance measurement indicators applied to the private sector depend on the entity's objectives, strategies, and the interests of external parties or stakeholders.